The Study of Ingavirin® as the Drug for Prophylaxis and Treatment of Postvaccinal Reactions on Teovac in Animal Models - N. K. Chernikova; S. V. Borisevich; A. L. Khmelev; S. A. Nimirskaya; S. A. Melnikov (Антибиотики и Химиотерапия, 2020)
The experiment on guinea pigs shows that Ingavirin, when administered orally in a single dose of 15 mg/kg on the 4 th day after vaccination with TEOVac, reduces accumulation of vaccine virus in organs and tissues of animals without affecting the immunogenicity of the vaccine. This efficacy is less pronounced when it is used together with TEOVac. When administered three times orally on days 6, 7, and 8 after immunization, Ingavirin reduces the level of vaccine virus in the blood, liver, and oral mucosa by a factor of 2 or more. Ingavirin is almost as effective as Arbidol, but less effective than Ridostin. These data indirectly indicate the possibility of using ingavirin along with ridostin to prevent post-vaccination reactions during immunization with TEOVac, and also give grounds to consider ridostin, ingavirin, and arbidol as a means of treating post-vaccination reactions.